Utility of S100A12 as an Early Biomarker in Patients With ST-Segment Elevation Myocardial Infarction - Zhang, Xiaolin; Cheng, Minghui; Gao, Naijing; Li, Yi; Yan, Chenghui; Tian, Xiaoxiang; Liu, Dan; Qiu, Miaohan; Wang, Xiaozeng; Luan, Bo; Deng, Jie; Wang, Shouli; et al. (Frontiers in Cardiovascular Medicine, 2021)
Importance: S100A12 is a calcium binding protein which is involved in inflammation and progression of atherosclerosis. Objective: We sought to investigate the utility of S100A12 as a biomarker for the early diagnosis and prognostication of patients presenting with ST-segment elevation myocardial infarction (STEMI). Design, Setting, and Participants: S100A12 was measured in 1023 patients presenting to the emergency department with acute chest pain between June 2012 and November 2015. An independent cohort of 398 patients enrolled at 3 different hospitals served as a validation cohort. Main Outcomes and Measures: The primary clinical endpoint of interest was major adverse cardiac and cerebral events (MACCE) defined as a composite of all-cause death, MI, stroke, or hospitalization for heart failure. Results: A total of 438/1023 patients (42.8%) in the diagnosis cohort were adjudicated as STEMI, among whom plasma S100A12 levels increased within 30 min and peaked 1–2 h after symptom onset. Compared with high-sensitivity cardiac troponin T and creatine kinase-MB isoenzyme, S100A12 more accurately identified STEMI, especially within the first 2 h after symptom onset (area under the curve 0.963 compared with 0.860 for hscTnT and 0.711 for CK-MB, both P < 0.05). These results were consistent in the 243-patient validation cohort. The 1-year rate of MACCE was greatest in patients in the highest peak S100A12 tertile, intermediate in the middle tertile and least in the lowest tertile (9.3 vs. 5.7 vs. 3.0% respectively, Ptrend = 0.0006). By multivariable analysis the peak plasma concentration of S100A12 was an independent predictor of MACCE within 1 year after STEMI (HR, 1.001, 95%CI, 1.000–1.002; P = 0.0104). Conclusions and Relevance: S100A12 rapidly identified patients with STEMI, more accurately than other cardiac biomarkers, especially within the first 2 h after symptom onset. The peak plasma S100A12 level was a strong predictor of 1-year prognosis after STEMI.